Mutation-based detection and monitoring of cell-free tumor DNA in peripheral blood of cancer patients - Benesova, L; Belsanova, B; Suchanek, S; Kopeckova, M; Minarikova, P; Lipska, L; Levy, M; Visokai, V; Zavoral, M; Minarik, M (Analytical biochemistry, 2013)
Prognosis of solid cancers is generally more favorable if the disease is treated early and efficiently. A key to long cancer survival is in radical surgical therapy directed at the primary tumor followed by early detection of possible progression, with swift application of subsequent therapeutic intervention reducing the risk of disease generalization. The conventional follow-up care is based on regular observation of tumor markers in combination with computed tomography/endoscopic ultrasound/magnetic resonance/positron emission tomography imaging to monitor potential tumor progression. A recent development in methodologies allowing screening for a presence of cell-free DNA (cfDNA) brings a new viable tool in early detection and management of major cancers. It is believed that cfDNA is released from tumors primarily due to necrotization, whereas the origin of nontumorous cfDNA is mostly apoptotic. The process of cfDNA detection starts with proper collection and treatment of blood and isolation and storage of blood plasma. The next important steps include cfDNA extraction from plasma and its detection and/or quantification. To distinguish tumor cfDNA from nontumorous cfDNA, specific somatic DNA mutations, previously localized in the primary tumor tissue, are identified in the extracted cfDNA. Apart from conventional mutation detection approaches, several dedicated techniques have been presented to detect low levels of cfDNA in an excess of nontumorous (nonmutated) DNA, including real-time polymerase chain reaction (PCR), "BEAMing" (beads, emulsion, amplification, and magnetics), and denaturing capillary electrophoresis. Techniques to facilitate the mutant detection, such as mutant-enriched PCR and COLD-PCR (coamplification at lower denaturation temperature PCR), are also applicable. Finally, a number of newly developed miniaturized approaches, such as single-molecule sequencing, are promising for the future.
Keywords: mutační analýza DNA; DNA, Neoplasm; apoptóza; DNA nádorová; DNA Mutational Analysis; nádory; Mutation; mutace; Animals; lidé; Necrosis; Neoplasms; nekróza; Humans; zvířata; Apoptosis